2020
DOI: 10.1097/paf.0000000000000544
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic Multiple-Organ Fat Embolism

Abstract: The patient was an 88-year-old woman with a 10-year history of hypertension. She was suspected to have been hit by a car. At the time of the event, she was conscious and able to stand on her own and had no obvious injuries. She was sent home, but she lapsed into unconsciousness and was nonresponsive after 2 hours. She was sent to the hospital, and her heartbeat and breathing stopped. After half an hour of rescue attempts, her heartbeat did not recover, and she was declared dead. During the autopsy, a small sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Signi cantly minor adipose tissue injury in the presence of trauma is an indication of death from nontraumatic pulmonary fat embolism. Examinations of sites for fat emboli should include each major organ [3] as well as the peripheral arterial system and the venous system draining from noninjured sites to identify the possible source of the fat embolus. It has been reported that biochemical testing of the deceased's cardiac blood should be performed, with attention to abnormal changes in VLDL, cholesterol, TG, FFA, and CRP [3].…”
Section: Differential Diagnosis Of Fat Embolism Sourcementioning
confidence: 99%
See 4 more Smart Citations
“…Signi cantly minor adipose tissue injury in the presence of trauma is an indication of death from nontraumatic pulmonary fat embolism. Examinations of sites for fat emboli should include each major organ [3] as well as the peripheral arterial system and the venous system draining from noninjured sites to identify the possible source of the fat embolus. It has been reported that biochemical testing of the deceased's cardiac blood should be performed, with attention to abnormal changes in VLDL, cholesterol, TG, FFA, and CRP [3].…”
Section: Differential Diagnosis Of Fat Embolism Sourcementioning
confidence: 99%
“…Examinations of sites for fat emboli should include each major organ [3] as well as the peripheral arterial system and the venous system draining from noninjured sites to identify the possible source of the fat embolus. It has been reported that biochemical testing of the deceased's cardiac blood should be performed, with attention to abnormal changes in VLDL, cholesterol, TG, FFA, and CRP [3]. Lipid analysis of fat emboli, if necessary, may also be performed, which may suggest a possible mechanism of pulmonary fat embolism formation [4].…”
Section: Differential Diagnosis Of Fat Embolism Sourcementioning
confidence: 99%
See 3 more Smart Citations